Occurrence, distribution, and potential ecological risks of psychoactive substances in the mangrove environment, Hainan Island of South China - Junnan Chen; Dan Feng; Jian Xu; Guoliang Ren; Changsheng Guo; Xiaocong Cao; Anfu Yang; Li Wang; Mingyang Wang; Ruixian Wang; Like Chen; Xiaochen Wu (Environmental Sciences Europe)
Abstract Background As a kind of emerging contaminant, psychoactive substances (PSs) have been detected in different types of freshwater ecosystems; however, their occurrence in coastal shore areas is seldom reported. In this study, surface water samples from the mangrove ecosystems across 6 cities and counties in Hainan Island, 68 water samples were collected from August to December 2022, for assessment of the occurrence, spatial distribution, and potential ecological risks of PSs in the mangrove ecosystem in Hainan Island, South China. Results A total of 13 PSs were determined by liquid chromatography–mass spectrometry (LC–MS), with 7 of them at high frequency (> 50%). Amphetamine (AMP) was detected with the highest concentration of 12.0 ng/L, followed by ephedrine (EPH) of 8.31 ng/L. The spatial distribution showed that PSs concentrations in mangroves in the Eastern Route were higher than those in the Western Route, similar to the level of regional development, which may be influenced by seasonal tourism. The risk quotients (RQs) of the PSs ranged from 0 to 0.0055, suggesting the low risk of PSs in Hainan mangrove ecosystems. Conclusions Generally, this study provided valuable insights into the environmental occurrence, spatial variations, and ecological risks of PSs in mangrove wetlands systems for the first time, serving as a foundation for understanding their influence on the mangrove ecosystem, which may aid in protection of those unique and vulnerable areas.